The multiple phenotypes of allosteric receptor mutants. - Galzi, J L (1996)
Channel-linked neurotransmitter receptors are membrane-bound heterooligomers made up of distinct, although homologous, subunits. They mediate chemo-electrical signal transduction and its regulation via interconversion between multiple conformations that exhibit distinct pharmacological properties and biological activities. The large diversity of functional properties and the widely pleiotropic phenotypes, which arise from point mutations in their subunits (or from subunit substitutions), are interpreted in terms of an allosteric model that incorporates multiple discrete conformational states. The model predicts that three main categories of phenotypes may result from point mutations, altering selectively one (or more) of the following features: (i) the properties of individual binding sites (K phenotype), (ii) the biological activity of the ion channel (gamma phenotype) of individual conformations, or (iii) the isomerization constants between receptor conformations (L phenotype). Several nicotinic acetylcholine and glycine receptor mutants with complex phenotypes are quantitatively analyzed in terms of the model, and the analogies among phenotypes are discussed.